New data on winter feeding and migrations of pacific salmon in the Sea of Okhotsk and in the Pacific waters of Kuril Islands - A. N. Starovoitov; D. N. Chulchekov; A. S. Hleborodov (Известия ТИНРО, 2022)
The results of trawl surveys in the Sea of Okhotsk and in the Pacific waters of Kuril Islands at the R/V «Professor Kaganovskii» in the winter 2021 are analyzed. These studies provide data on spatial distribution, abundance and biomass of fishes, cephalopods and jellyfishes in the epipelagic layer of the Sea of Okhotsk and in the Pacific waters of Kuril Islands The analysis of the contemporary status of epipelagic nekton communities of the Pacific waters and one of the Okhotsk Sea near Kuril Islands is provided. Quantitative distribution and biological state of all Pacific salmon in the winter season is reviewed in full detail.